Pengaruh Lingkungan Kerja Fisik, Work Life Balance, dan Kepuasan Kerja terhadap Kinerja Karyawan : (Studi pada Karyawan Grand Serela Hotel Bandung) - Gabriel Sara Tesalonika; Yuni Kasmawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the influence of the physical work environment (X1), work-life balance (X2), and job satisfaction (X3) on employee performance (Y) at Grand Serela Hotel Bandung. The method used in this study is a non-probability technique with saturated sampling, with a population of 56 hotel employees. Data analysis was carried out using multiple linear regression, assisted by SPSS version 25 and Microsoft Excel 2019. The results showed that the physical work environment (X1) has a significant influence on employee performance (Y), which indicates that the physical condition of the workplace can increase employee productivity and performance. However, work-life balance (X2) does not have a significant effect on employee performance, which may indicate that other factors outside of work-life balance affect employee performance. Job satisfaction (X3) also has a significant effect on employee performance, indicating that a high level of job satisfaction can improve overall employee performance. This study provides insights for hotel management to improve employee performance through improving the work environment and increasing job satisfaction.